Histological features of the structure of the long head of biceps brachii tendon in patients with concomitant injuries of the rotator cuff - D. O. Kolmakov; N. V. Zagorodniy; A. V. Korolev; D. O. Ilyin; O. G. Ushkova (Acta Biomedica Scientifica, 2024)
Background. The long head of biceps brachii tendon plays an important role in shoulder pain. Surgical tactics remain controversial. There are two approaches: tenotomy of the long head of biceps brachii tendon and tenodesis. Both have positive and negative sides. There is also no consensus on the effective position for performing tenodesis.The aim. To assess the histological structure of various parts of the long head of biceps brachii tendon, which may be the causes for persistent pain syndrome.Materials and methods. In this study, we examined the histological structure of the long head of biceps brachii tendon in 12 patients aged 18–59 years having chronic anterior shoulder pain with concomitant damage to the supraspinatus and subscapularis tendons. In all cases, magnetic resonance imaging (MRI) revealed changes that made it impossible to perform intraarticular tenodesis. Patients were divided into two groups according to the World Health Organization classification: young (18–44 years) and middle-aged (45–59 years). All patients underwent arthroscopy with subpectoral tenodesis and correction of concomitant pathology. The obtained macropreparations are divided into three zones: the proximal zone, the intertubercular zone and the zone below the intertubercular groove. All macropreparations were sent for histological examination.It was revealed that the most common changes occur in the area of the intertubercular groove in all categories, however, in the middle-aged group, the signs of inflammation and degeneration are equally evident in this zone and in the proximal part of the tendon.Conclusions. Young and middle-aged patients with damage to the tendons of the supraspinatus and subscapularis muscles and signs of chronic tendinitis of the long head of biceps brachii tendon tendon and pronounced structural changes according to MRI should undergo a subpectoral tenodesis procedure; it is also necessary to take into account the anatomical features of the tendon and possible surgical risks.